2020
DOI: 10.1111/coa.13499
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal stimulation in children with inner ear malformation: One side cochlear implant and contralateral auditory brainstem implant

Abstract: Objective To determine audiological outcomes of children who use a cochlear implant (CI) in one ear and an auditory brainstem implant (ABI) in the contralateral ear. Design Retrospective case review. Setting Tertiary referral hospital. Participants Twelve children followed with CI and contralateral auditory brainstem implant (ABI) by Hacettepe University Department of Otorhinolaryngology and Audiology in Turkey. All children were diagnosed with different inner ear malformations with cochlear nerve aplasia/hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
1
17
0
4
Order By: Relevance
“…Cochlear nerve deficiency is common in children with CH, so, if auditory perception and language development with CI are limited, contralateral side ABI should be considered without delay. 4,19 In our study, all IP-I, 20 Tucci et al 21 Auditory perception and speech production vary across IEMs.…”
Section: Discussionmentioning
confidence: 51%
“…Cochlear nerve deficiency is common in children with CH, so, if auditory perception and language development with CI are limited, contralateral side ABI should be considered without delay. 4,19 In our study, all IP-I, 20 Tucci et al 21 Auditory perception and speech production vary across IEMs.…”
Section: Discussionmentioning
confidence: 51%
“…Batuk et al report a case series of 12 children who received auditory brainstem implant after poor hearing outcomes with CI alone. They found a common CVN in cases of CC and report one case of CA with a hypoplastic CN 24 . Monsanto et al found a hypoplastic CN in 66% of their cases with CA 23 .…”
Section: Discussionmentioning
confidence: 94%
“…As a sidenote, the assumed CC was further analyzed concerning its size. In cases that present inconclusive anatomy or hypoplastic CN, the decision between ABI and CI is reported to be challenging, and as a first‐approach CI is still recommended 24 . In patients with CC, the neural elements have been described as present along the medial wall of the CC.…”
Section: Discussionmentioning
confidence: 99%
“…However, ABI users could identify few words using the auditory sensations provided by the device alone (not more that 20% of words in simple sentences; Colletti et al, 2012). Batuk et al (2020) investigated the bimodal stimulation of children who have inner ear malformation and found that the coherent use of CIs and ABIs increased performance and speech perception. In another study on the efficacy of ABIs, for improvement of speech perception and audiometry tests in patients with post meningitis hearing loss, there was an increase in hearing performance post implantation of the device (Malerbi et al, 2018).…”
Section: Auditory Implantsmentioning
confidence: 99%